Digital twin demonstrates significance of biomechanical growth control in liver regeneration after partial hepatectomy - Höhme, Stefan; Hammad, Seddik; Boettger, Jan; Begher-Tibbe, Brigitte; Bucur, Petru; Vibert, Eric; Gebhardt, Rolf; Hengstler, Jan G.; Drasdo, Dirk (iScience, 2023)
Partial liver removal is an important therapy option for liver cancer. In most patients within a few weeks, the liver is able to fully regenerate. In some patients, however, regeneration fails with often severe consequences. To better understand the control mechanisms of liver regeneration, experiments in mice were performed, guiding the creation of a spatiotemporal 3D model of the regenerating liver. The model represents cells and blood vessels within an entire liver lobe, a macroscopic liver subunit. The model could reproduce the experimental data only if a biomechanical growth control (BGC)-mechanism, inhibiting cell cycle entrance at high compression, was taken into account and predicted that BGC may act as a short-range growth inhibitor minimizing the number of proliferating neighbor cells of a proliferating cell, generating a checkerboard-like proliferation pattern. Model-predicted cell proliferation patterns in pigs and mice were found experimentally. The results underpin the importance of biomechanical aspects in liver growth control.
Online verfügbar: 5. Dezember 2022, Artikelversion: 12. Januar 2023
Gesehen am 29.08.2024